1987
DOI: 10.1007/bf00148787
|View full text |Cite
|
Sign up to set email alerts
|

Quiet Sun and slowly varying component at meter and decameter wavelengths

Abstract: Comparison of maps of the Sun obtained over the period June 29 to July 8, 1982 at 169 MHz with the Nan~ay Radioheliograph and at 73.8, 50, and 30.9 MHz with the Clark Lake Radioheliograph shows that the slowly varying component at meter and decameter wavelengths is not always thermal emission. During the period under study weak noise storm continua were the most frequent sources of slowly varying component at 169 and 73.8 MHz. Most filaments show no radio counterpart on the disk. A streamer has been detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
16
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
(3 reference statements)
9
16
0
Order By: Relevance
“…These results provide a quantitative verification of the qualitative assessment of Alissandrakis, Lantos, and Nicolaidis (1985) and Lantos et al (1987). A similar relation also exists between metric radio sources and Boulder filaments.…”
Section: Statistical Analysis Of Radio Source Filament and Neutral Lsupporting
confidence: 77%
See 2 more Smart Citations
“…These results provide a quantitative verification of the qualitative assessment of Alissandrakis, Lantos, and Nicolaidis (1985) and Lantos et al (1987). A similar relation also exists between metric radio sources and Boulder filaments.…”
Section: Statistical Analysis Of Radio Source Filament and Neutral Lsupporting
confidence: 77%
“…These results were largely confirmed by subsequent observations (Lantos et al, 1987;Lantos, Alissandrakis, and Rigaud, 1992), however no systematic study of possible associations was ever made.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Holes can be either darker or brighter than the mean disk at 150 MHz, and the question of their aspect at lower frequencies remains open. Do they systematically become brighter than the disk at low frequencies, as seen by Lantos et al (1987) in one case observed at 37 and 75 MHz with the CLRO radioheliograph? It would also be interesting to investigate whether the bright elongated structures we observe at 150 MHz present a different aspect at still lower frequencies.…”
Section: Discussionmentioning
confidence: 94%
“…They show more contrast at 408 MHz (about 50% of the QS) than at lower frequencies. Most of them are still visible at 169 MHz as shallow depressions (10-20%), more rarely at 80 MHz and at lower frequencies, where they can occasionally appear as faint brightness enhancements (Lantos et al 1987). Because of the limited resolution and dynamic range in images, the shapes in radio and EUV could not be precisely compared.…”
Section: Introductionmentioning
confidence: 99%